Infliximab‐Induced Aseptic Meningitis in a Patient with Crohn's Disease. Issue 1 (2018) - Junga, Zachary; Theeler, Brett; Singla, Manish
ABSTRACT : N/A: Infliximab is an anti‐tumor necrosis factor α (TNFα) monoclonal antibody that treats moderate‐to‐severe Crohn's disease. In rare cases, infliximab has been associated with drug‐induced aseptic meningitis. We present a 46‐year‐old woman with migraines and inflammatory Crohn's colitis treated with intravenous infliximab and methotrexate. She developed nuchal rigidity, photophobia, and headache 2 days after each of her infliximab infusions, with symptom resolution 1 week post‐infusion. Her exam, imaging, and cerebrospinal fluid analysis were consistent with drug‐induced aseptic meningitis. She discontinued infliximab and started vedolizumab with continued remission of her Crohn's disease.